KEARIFAN TRADISIONAL DAN KEHIDUPAN BERKELANJUTAN (Studi kasus kearifan tradisional masyarakat suku Dayak Tamambaloh di Kalimantan Barat dan suku Sentani Putali di Papua) - Damayanti, Christy (Transformasi, 2012)
Abstract Traditional knowledge is a fundamental understanding that a community is defined as all parts of the ecosystem, or ecological community, not a human social communities like the West in view. Country, modern institution established on the concept and model of Western society, comes in with the ideology of developments indigenous peoples who do not include environmental and socio-cultural wealth preservation as an integral part of the entire development process. Sustainability of life there will be only through the understanding that human beings are merely biological beings, the same as any other biological creatures, Humans inhabit the same earth inhabited by other beings. Keyword: State; Development; Ecological; Community